UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT MELALUI PELATIHAN DAN PENDAMPINGAN UMKM BERBASIS MASJID DI SURABAYA - Irfan Ramis; Moh Farih Fahmi; Sri Abidah Suryaningsih; A’rasy Fahrullah (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
Kedurus Village, located in the Karangpilang District of Surabaya City, boasts a diverse community and significant economic potential. One of the challenges encountered is the community's and worshippers' absence of interest in entrepreneurship in the vicinity of the Gunung Sari Indah Mosque. Training and mentoring for Micro, Small, and Medium Enterprises (MSMEs) based on mosques are viable strategies for enhancing the economy of the community in Kedurus Village. An effective solution to support the economic development of the community is anticipated to be the collaboration between the local administration and the Indonesian Mosque Council (DMI) of Surabaya City. The development of micro, small, and medium-sized enterprises (MSMEs) is essential for the establishment of sustainable economic growth at the local level. MSMEs are instrumental in the development of employment opportunities, the expansion of the economy, and the enhancement of community welfare. MSMEs can enhance the quality of their products, digital marketing, digital financial management, and other aspects that facilitate business growth through appropriate training and mentoring. Mosques, which serve as hubs for religious and social activities, possess significant potential to serve as hubs for the development of micro, small, and medium-sized enterprises. The function of mosques as agents of economic development at the local level will be enhanced through collaboration with the Indonesian Mosque Council (DMI) of Surabaya City. The government, religious institutions, and community are expected to establish a positive synergy through the participation of mosques in community service activities.